Computational Linguistics and Intelligent Text Processing 10th International Conference, CICLing 2009, Mexico City, Mexico, March 1-7, 2009. Proceedings - Gelbukh, Alexander. (Lecture Notes in Computer Science, 2009)
This book constitutes the refereed proceedings of the 10th International Conference on Computational Linguistics and Intelligent Text Processing, CICLing 2009, held in Mexico City, Mexico in March 2009. The 44 revised full papers presented together with 4 invited papers were carefully reviewed and selected from numerous submissions. The papers cover all current issues in computational linguistics research and present intelligent text processing applications.